Lavengro: The Scholar, the Gypsy, the Priest - Borrow, George, 1803-1881; Knapp, William I. (William Ireland), 1835-1908 (Salt Lake City, UT : Project Gutenberg, 2007)
"Lavengro: The Scholar, the Gypsy, the Priest" by George Borrow is a work published in 1851 that blends memoir and novel. The protagonist George, son of a militia officer, grows up in barrack towns across Britain and Ireland. His journey takes him from lawyer's apprentice to London hack writer to wandering tinker, encountering Romany travelers along the way. This classic of 19th-century English literature offers vivid portraits of outcasts and adventurers on the margins of Victorian society. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lavengro
Release date is 2007-11-01
Transcribed from the 1911 John Murray edition, by David Price
Keywords: England -- Fiction; Romanies -- Fiction